The new positioning : the latest on the world's #1 business strategy - Trout, Jack; Rivkin, Steve (New York, 1996)
It's the most famous, most quoted, most misunderstood business strategy of all time. Positioning is not what you do to the product. It's what you do to the mind. But how do you get into a crowded 1990s mind? What if somebody already owns your concept? And what has an era of tumultuous change done to positioning? The New Positioning is the first new body of thought in more than a decade on the world's most famous business strategy - written by Jack Trout, the author and marketing strategist who started it all, and Steve Rivkin. The breakthrough 1981 book Positioning: The Battle for Your Mind became a global best-seller in 19 languages. Now its provocative sequel promises to open even more eyes. Packed with keen insight, penetrating analysis, and irreverent advice, The New Positioning delivers hundreds of examples, anecdotes, and case studies - on computers, oil companies, television shows, soft ice cream, even political candidates.
Keywords: Positioning ( Advertising)